2021
DOI: 10.3389/fpsyt.2021.700774
|View full text |Cite
|
Sign up to set email alerts
|

Defense Mechanisms and Borderline Personality Organization Among COVID-19 Believers and Non-believers During Complete Lock-Down

Abstract: The aim of the current study was to investigate whether a specific social perception of the pandemic—believing or not in COVID-19—predicts borderline personality organizations and whether this relationship is mediated by more primitive maladaptive mechanisms—splitting, denial, and dissociation. The online study included 720 organization aged 25–45. Participants were diverse in terms of place of residence, being in a relationship, and education level. Approximately 30% of the general population reported not bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…An online Polish study of 720 individuals from the general population examined people who did not believe in the existence of COVID-19 and found that these ‘nonbelievers’ were more likely to show characteristics of borderline personality organisation and use maladaptive defence mechanisms, especially splitting [ 22 ].…”
Section: Personality Disorders and Covid-19 Pandemicmentioning
confidence: 99%
“…An online Polish study of 720 individuals from the general population examined people who did not believe in the existence of COVID-19 and found that these ‘nonbelievers’ were more likely to show characteristics of borderline personality organisation and use maladaptive defence mechanisms, especially splitting [ 22 ].…”
Section: Personality Disorders and Covid-19 Pandemicmentioning
confidence: 99%
“…The panel is actively updated to be representative of the adult Polish population. Data collection through the Ariadna online survey methodology (using a dedicated IT system) has been used in previously published papers [27][28][29].…”
Section: Study Design and Populationmentioning
confidence: 99%
“…A similar pattern seems to be applicable to less educated people who tend to ignore scientific methods and embrace pseudo-scientific theories instead [ 13 , 14 , 15 ]. From this perspective, the overwhelming stress and sense of hopelessness associated with the outbreak could be temporarily alleviated through immature defensive mechanisms, such as dissociation, which would reduce awareness of intolerable information [ 16 , 17 ]. Some research has indicated that belief in conspiracy theories could be increased by dissociation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%